A household-level decomposition of the white-black homeownership gap - FESSELMEYER, Eric (Institutional Knowledge at Singapore Management University, 2012)
This paper uses a semiparametric homeownership model to estimate and to decompose the household-level white-black homeownership gap into an endowment component and a residual component across the distribution of homeownership rates. We find that the racial gap differs across homeownership rates and that studies that examine the gap only at the mean may be misleading. We also find that although household characteristics explain the homeownership gap for most households, there is a substantial portion of the gap that remains unexplained for households with a very low propensity to own homes. A comparison of the estimates from the semiparametric model and a probit model suggests that the semiparametric approach is able to capture the heterogeneity structure between the ethnic groups, particularly in the tails of the distribution. To illustrate the flexibility of our household-level approach, we decompose the homeownership gap in cities of varying levels of segregation.